Uses And Gratification: Uji Pengaruh Konten dalam Fitur Tiktok Shop Terhadap Perilaku Konsumtif Belanja - Ade Ayu Oktaviani; Siti Komsiah; Syaifuddin Syaifuddin (Universitas Persada Indonesia YAI, 2022)
Humans have several needs that must be met in living life, but with advances in technology,communication, and industry making the current shopping system more accessible and reachable, namelyshopping through social media, currently TikTok is launching a new feature called Tiktok Shop which canhelp users in selling and buying products from the Tiktok application, but over time human needs for goodsand services will experience changes, these changes are caused by human nature to be dissatisfied with whatis obtained, therefore rising the consumptive behavior in shopping. The purpose of this study was to determinewhether there is an effect of content in the TikTok Shop feature on online shopping consumptive behavior.The theory used in this study is the uses and gratification theory which focuses on the audience when decidingthe use of media based on motives and interests to meet needs in achieving a goal. This study uses aquantitative approach, with the type of explanatory research, while the method used is a survey method bydistributing questionnaires. The results showed that the effect of content has a significant correlation toconsumptive behavior, and has an effect of 24.4% on consumptive behavior. While the remaining 75.6% isinfluenced by other variables outside of this study.